Succession Planning and Employee Retention in Public Organisations in Uganda: A Case Study of Uganda National Roads Authority - Mazin Anwar (Uganda Christian University, 2024)
This study investigated the impact of succession planning on employee retention in public organizations, with a specific focus on the Uganda Revenue Authority (UNRA) in Kampala. It examined three key variables: talent identification, capacity building, and team leadership, and their influence on employee retention. Data was collected through surveys and interviews with UNRA staff, and was analyzed using Pearson's correlation and regression analysis. The findings revealed a significant positive relationship between talent identification, capacity building, team leadership, and employee retention. Talent identification, capacity building, and effective team leadership were found to have played crucial roles in improving retention rates. The study recommended enhancing talent identification practices, increasing capacity-building efforts, and strengthening team leadership within public organizations. The research highlighted the importance of succession planning as a strategic tool for retaining valuable employees and improving organizational performance. Further research was suggested to extend the findings across different sectors and over longer timeframes.
Undergraduate research